2019
DOI: 10.1177/0272431619891244
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Teachers’ Academic and Behavioral Perceptions of Their Students and Expectations for High School Graduation

Abstract: Teacher expectations of students have been consistently linked with student academic achievement. What is less known is how students’ actual behaviors and performance shape teachers’ perceptions of them, particularly when considering student gender and race/ethnicity. A diverse dyadic sample of 1,653 seventh graders with 63 reporting teachers was used to examine how teaching experience, student behavioral citations, and grade point average were related to teachers’ perceptions of each student’s antisocial beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
(85 reference statements)
2
3
0
Order By: Relevance
“…The findings from interviews show that the various school based measures put in place to check indiscipline had resulted in positive discipline outcomes among the students studied. These findings agree with the study by Williams et al (2019) who posits that there was "a positive link between disciplinary actions and behavioural outcomes among students." Students responded positively to interventions put in place to check their discipline and this had created a conducive leaning environment in the schools.…”
Section: Students' Disciplinesupporting
confidence: 92%
See 1 more Smart Citation
“…The findings from interviews show that the various school based measures put in place to check indiscipline had resulted in positive discipline outcomes among the students studied. These findings agree with the study by Williams et al (2019) who posits that there was "a positive link between disciplinary actions and behavioural outcomes among students." Students responded positively to interventions put in place to check their discipline and this had created a conducive leaning environment in the schools.…”
Section: Students' Disciplinesupporting
confidence: 92%
“…The findings further show that the students discipline was changing positively due to the discipline interventions put in place in the schools, further supporting the findings by Williams et al (2019). As such, it was Licensed Under Creative Commons Attribution (CC BY-NC) pertinent to reinforce disciplinary actions in the schools since this had positive implications on the discipline of the students.…”
Section: Students' Disciplinesupporting
confidence: 75%
“…Similarly, when kids performed better academically, teachers viewed them more warmly. However, various subtleties were discovered based on student gender and race/ethnicity, indicating potentially substantial impact of instructor expectations on student results (Williams, 2020). All of factors influencing teachers' behavior are highly correlated with one another and with students' academic achievement, but there is a positive but weak relationship between two factors: rules, routine, and support, and negative behavior.…”
Section: Teachers Academic Behaviormentioning
confidence: 99%
“…This, in turn, influences children and adolescents’ self-concepts and task values (e.g., motivational beliefs) which influences youth subsequent behaviors. For example, Williams et al (2020) found that student behaviors typically co-occurring with grade retention (e.g., low academic achievement, antisocial behaviors; Lorence, 2006; Rodney, Crafter, Rodney, & Mupier, 2010) were significantly linked with teachers’ expectations that students would graduate from high school. In this study, the students’ gender and race/ethnicity were important moderators of teacher expectations and may be important considerations in understanding grade retention and dropout risk (Williams et al, 2020).…”
mentioning
confidence: 99%
“…For example, Williams et al (2020) found that student behaviors typically co-occurring with grade retention (e.g., low academic achievement, antisocial behaviors; Lorence, 2006; Rodney, Crafter, Rodney, & Mupier, 2010) were significantly linked with teachers’ expectations that students would graduate from high school. In this study, the students’ gender and race/ethnicity were important moderators of teacher expectations and may be important considerations in understanding grade retention and dropout risk (Williams et al, 2020). Furthermore, perceived criticism from trusted adults plays a major role in adolescents’ self-perceptions, which shapes their psychosocial, behavioral, and achievement outcomes (Cohen & Frydenberg, 1996; Cross, 1997).…”
mentioning
confidence: 99%